Comprehensive assessment of the psycho-emotional state of pregnants, taking into account the psychosomatic component - Siusiuka, V. H.; Deinichenko, O. V.; Pavliuchenko, M. I.; Onopchenko, S. P.; Lyubomirska, K. S.; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна; Павлюченко, Михайло Іванович; Онопченко, Світлана Павлівна; Любомирська, Катерина Сергіївна (Boston : Primedia eLaunch, 2024)
The purpose of the work: to give a comprehensive assessment of the psycho-emotional state of pregnant women in the II and III trimesters (screening), taking into account the psychosomatic component.